Safe long-term therapy of Cushing’s syndrome over 37 years with mitotane - Seibold, Jonas; Hönemann, Mario; Tönjes, Anke; Sandner, Benjamin (Frontiers in Endocrinology, 2024)
While suggested, surgery is not always possible as a first-line treatment of Cushing’s Disease (CD). In such cases, patients require medical therapy in order to prevent complications resulting from hypercortisolism. Although there has been a wide expansion in pharmacological options in recent years, mitotane was the agent of choice for treating hypercortisolism decades ago. Due to the introduction of other therapies, long-term experience with mitotane remains limited. Here, we report the case of a woman with CD who was treated with mitotane for 37 years. During the treatment period, biochemical and clinical disease control was achieved and the patient had two uncomplicated pregnancies. Drug-related side effects remained moderate and could be controlled by several dose adjustments. Our case highlights the ability of mitotane to allow an effective control of hypercortisolism and to represent a safe treatment option in special situations where CD requires an alternative therapeutic approach. Furthermore, we provide a literature review of the long-term use of mitotane and reported cases of pregnancy in the context of mitotane therapy.